2007
DOI: 10.1152/ajpendo.00365.2006
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of nitric oxide to cutaneous microvascular dilation in individuals with type 2 diabetes mellitus

Abstract: Sokolnicki LA, Roberts SK, Wilkins BW, Basu A, Charkoudian N. Contribution of nitric oxide to cutaneous microvascular dilation in individuals with type 2 diabetes mellitus. Am J Physiol Endocrinol Metab 292: E314 -E318, 2007. First published September 5, 2006; doi:10.1152/ajpendo.00365.2006.-Microvascular pathophysiology associated with type 2 diabetes mellitus (T2DM) contributes to several aspects of the morbidity associated with the disease. We quantified the contribution of nitric oxide (NO) to the cutaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
72
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 19 publications
(37 reference statements)
3
72
1
2
Order By: Relevance
“…6 This underlying defect was present despite normal increases in interstitial NO in the foot dorsum under stimulated conditions, suggesting that NO is either ineffective or not significantly involved in this acute response. 3 A prior bout of acute maximal exercise also appears to improve responsiveness to local heating of the dorsal foot in active individuals with T2DM, but not in their sedentary counterparts. 7 These previous studies have suggested that participation in chronic aerobic training may regulate stimulated (heated) dorsal foot skin perfusion through alterations in either PG or EDHF pathways, given that interstitial cutaneous NO levels (measured via a subcutaneous probe) are not apparently significantly depressed by the presence of T2DM.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…6 This underlying defect was present despite normal increases in interstitial NO in the foot dorsum under stimulated conditions, suggesting that NO is either ineffective or not significantly involved in this acute response. 3 A prior bout of acute maximal exercise also appears to improve responsiveness to local heating of the dorsal foot in active individuals with T2DM, but not in their sedentary counterparts. 7 These previous studies have suggested that participation in chronic aerobic training may regulate stimulated (heated) dorsal foot skin perfusion through alterations in either PG or EDHF pathways, given that interstitial cutaneous NO levels (measured via a subcutaneous probe) are not apparently significantly depressed by the presence of T2DM.…”
Section: Introductionmentioning
confidence: 95%
“…Among the vasodilators are nitric oxide (NO), prostacyclins, prostaglandins (PG), bradykinin, and endothelial-derived hyperpolarizing factor (EDHF), which appear to vary in importance depending on their cutaneal location. [1][2][3][4] Delivery of nutrients, removal of metabolic waste, temperature regulation, and healing are all affected by maintenance of skin perfusion, but when type 2 diabetes mellitus (T2DM) has an underlying presence, alterations in foot skin perfusion may result in a greater risk of ulceration and poor cutaneous healing. 3 Colberg et al Previously, it has been postulated that participation in chronic aerobic training (ie, regular exercise for longer than six months) improves stimulated dorsal foot skin perfusion through local release of vasodilatory compounds including NO, PG, and EDHF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] Tem sido ainda utilizada como um modelo de investigação em vários estados patológi-cos como a diabetes do tipo II, [6] a doença vascular periférica [1] e a hipertensão [7] . No contexto clínico as variáveis microcirculatórias são utilizadas como ferramentas de prognóstico para avaliar a isquémia grave dos membros [8] , a evolução da ferida cutânea [9] e, até para determinar o nível de amputação.…”
Section: Introductionunclassified
“…[3][4][5] It has been used as a research model in various diseases such as type II diabetes [6] peripheral vascular disease [1] and hypertension. [7] Clinically, microcirculatory variables are also used as prognostic tools to assess severe limb ischemia, [8] wound outcome [9] and also to eventually determine the amputation level.…”
Section: Introductionmentioning
confidence: 99%